Teknik Dasar Histologi pada Ikan Gurami (Osphronemus gouramy) [ The Basic Histology Technique of Gouramy Fish (Osphronemus gourami)] - Abdul Manan; Harini Citra Pratiwi (Faculty of Fisheries and Marine Universitas Airlangga, 2015)
Abstract Histology is science that learns about cell,organ, and body tissues in a microscopic condition. Whereas science that learns about morbidity or patology of a tissue that's called as histopatology. Both of normal tissue's structure and abnormal tissue's stucturecan be learned by microscopic in a tissue preparation. This preparation made through processing of tissue until the preparation coloured. Then histology's structure can be watched clearly so that make it easy to read. Field Work Practice purpose (PKL) this is to know the basic histoloy technique in fish. This Field Work Practice was held in Balai Uji Standar Karantina Ikan Pengendalian Mutu dan Keamanan Hasil Perikanan (BUSKIPM) Jl. Harapan I No. 01A Cilangkap, East Jakarta on 14th January 2013 until 14th February 2013. The method of this Field Work Practice is descriptive method by collecting data through primary data and secondary data. The histology technique in fish are tissue fixation, trimming (tissue selection), tissue dehydration, the tissue block making, tissue cutting, tissue colouring, and tissue observation. From the result got from the gourami's tissue, there are edema and infestation of metacercaria parasites and myxosporidia in gill normal intestine tissue, normal liver tissue, and normal spleen tissue